Transitioning Preterm Infants From Parenteral Nutrition: A Comparison of 2 Protocols. (18th August 2016) - Miller, Malki; Donda, Keyur; Bhutada, Alok; Rastogi, Deepa; Rastogi, Shantanu
Abstract : Background: Growth in preterm infants is compromised during the transition phase of nutrition, when parenteral nutrition (PN) volumes are weaned with advancing enteral nutrition (EN) feeds, likely due to suboptimal nutrient intakes during this time. We implemented new PN guidelines designed to maintain optimal nutrient intakes during the transition phase and compared growth outcomes of this cohort with a control group. Materials and Methods: A chart review was conducted on infants born <32 weeks' gestation, before (control group) and after (study group) a new transition PN protocol was implemented in the neonatal intensive care unit. Weight parameters and nutrient intakes were calculated for the transition phase and compared between the 2 groups. Results: Demographic and clinical characteristics of the 2 groups were comparable except for higher rates of sepsis in control group. Weight‐for‐age z scores at birth, at 1 week of life, and at the start of the transition phase were similar. At the end of the transition phase, infants in the study group had significantly higher z scores compared with the control group, even when corrected for sepsis, a difference that persisted at 35 weeks' gestation. During the transition phase, study infants gained 16.1 ± 4.6 g/kg/d compared with 13.2 ± 5.4 g/kg/d in control group ( P < .001). Similar results were observed in the subset of expressed breastmilk–only fed infants (15.9 ± 4.6 g/kg/d in the study group compared with 13.2 ± 5.4 g/kg/d in the control group, P < .004). Conclusion: Optimizing nutrition by the use of concentrated PN during the transition phase to maintain appropriate nutrient intakes improves growth rates in preterm infants.